ssc student service corner - Puput Budi Wintoro; Deny Budiyanto; Resty Annisa (Universitas Harapan Bangsa, 2021)
Student service corner is an application designed as a student service system by utilizing a laravel framework in the Informatics Engineering study program, University of Lampung. The choice of Laravel as an application development framework at this time is because this application will continue to be developed with several programmers and will be integrated with other systems into a larger informatics study program. Data were collected by conducting interviews and literature studies. Data modeling in this system uses an entitty relationship diagram / ERD. The test result of this system is that the level of student satisfaction with services in the Information Engineering study program increases because it is always available because it is online. The admin of the study program can manage and request services for follow up. The results of this test show that the student service corner application can meet the system requirements as a communication between the the administration and students